THE EFFECT PRACTICAL TEACHING ON STUDENTA MOBILITY ABILITIES - Ratko Pavlović; Aleksandar Raković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
What is mostly known to us and it concerns the Physical Education are cybernetics transformation models by which we define certain ocurrences. Depending on the goal to be achieved, which we want to carry out, depends the way of leading and monitoring of the certain segment transformation of anthropological space of human. The research has been conclucted on the sample of 95 students, first year of studies. The effects of practical teaching of anthropomobility on mobility abilities have been studied during the semester. For the needs of the research 6 different variables have been applied. From this number five defined the complex strength space and one variable space flexibility. For obtaining the relevant information, univariant and multivariant variance analysis (ANOVA/MANOVA) has been applied, which comfirmed the positive effects of teaching, which confirmed statisticaly significant abilities transformation in regared to initial condition of the tested.